Interplay between impaired brain structure and function in term newborns with congenital heart disease. (3rd June 2015) - Birca, A; Vakorin, VA; Madathil, S; Chau, V; Miller, SP; Doesburg, SM; Seed, M; Blaser, S; Nita, DA; Duerden, EG; Hickey, EJ; Hahn, CD
Abstract : Background: Term neonates with congenital heart disease (CHD) demonstrate a high incidence of white matter injury (WMI), together with increased average diffusivity and decreased fractional anisotropy (FA) on MR diffusion tensor imaging. EEG background activity is a robust measure of functional brain maturation that becomes less discontinuous, contains more fast activity and shows higher complexity of EEG patterns with increasing age. We sought to determine the association between structural brain abnormalities and functional brain maturation in term neonates with CHD. Methods: Thirteen term newborns with CHD underwent pre-operative MR imaging and continuous EEG recordings (cEEG). The proportion of cEEG with discontinuous vs. continuous background activity was quantified by visual analysis. During continuous epochs, we differentiated between two states: wakefulness/active sleep vs. quiet/transitional sleep, and applied algorithms to measure spectral power and EEG complexity. Results: Three patients had multifocal WMI which was associated with greater EEG background discontinuity (P<0.05). Moreover, lower white matter diffusivity was associated with higher power of fast activity (P<0.05 for wakefulness/active sleep EEG pattern), while higher white matter FA showed a trend toward being associated with increased EEG complexity (P<0.1 for quiet/transitional sleep pattern). Conclusions: In this series of term neonates with CHD, structural and microstructural white matter abnormalities are associated with impaired maturation of brain function.